STUDY REGARDING THE QUANTIFICATION OF RANKL LEVELS IN PATIENTS WITH CHRONIC PERIODONTITIS AND OSTEOPOROSIS - Irina-Georgeta Șufaru; Sorina-Mihaela Solomon; Liliana Păsărin; Maria Alexandra Martu-Stefanache; Alexandra Cornelia Oanță; Ioana Mârțu; Arina Ciocan-Pendefunda; Silvia Mârțu (Romanian Society of Oral Rehabilitation, 2017)
Introduction and aim: Osteoporosis, a systemic skeletal disease characterized by an inflammatory status, can enhance the inflammation on periodontal level, with severe alveolar bone loss. The study proposed an evaluation of local and systemic RANKL levels, pre- and post- periodontal therapy. Materials and method: The clinical study was conducted in patients with chronic periodontitis, divided in osteoporosis group and systemically healthy subjects. The clinical periodontal parameters were determined at baseline and after scaling and root planing. The RANKL levels were investigated pre-therapy in gingival crevicular fluid and post-therapy in serum. Results and discussion: The periodontal tissue loss and the crevicular fluid RANKL were significantly more severe in the osteoporosis group, as image of the local influence of an impaired skeletal system. Both groups had a positive response to the periodontal therapy, with low levels of clinical parameters and serum RANKL. Conclusions: Our results support the relationship between osteoporosis and periodontal inflammatory changes, which can be amended by the conventional therapy.